ANALISIS RENTABILITAS DAN PENYERAPAN TENAGA KERJA PADA AGROINDUSTRI KERIPIK SUKUN (Studi Kasus pada Perusahaan Keripik Sukun Karya Ayu di Desa Pusakanagara Kecamatan Baregbeg Kabupaten Ciamis) - Rohendi Rohendi; Dini Rochdiani; Zulfikar Noormansyah (Jurnal Ilmiah Mahasiswa Agroinfo Galuh, 2017)
This study aims to find out : 1) The amount of cost, revenue, income and R / C at breadfruit chips agroindustry in one production process, 2) The amount of rentability in breadfruit chips agroindustry in one production process, and 3) The amount of labor absorption on breadfruit chips agroindustry. The method used in this research was a case study. Withdrawal of the respondents in this study used proposive sampling a company breadfruit chips in Pusakanagara village Sub-district Baregbeg Ciamis regency. Result of research on breadfruit chips agroindustry in one production process shows that from the row material of breadfruit as much as 200 pieces of breadfruit at price Rp. 5.000,00 per fruit, resulting in breadfruit chips as much as 150 kologram, selling price of breadfruit chips per kilogram Rp. 25.000, 00. Based on thecalculation results are known: 1) Crafters cost Rp. 2.193.931,00, resulting in revenue of Rp. 6.150.000,00, income of Rp.3.931.068,45 and R / C value of 2,8. 2) Rentability generated by 1,79 percent of total cost incurred. 3) The amount of labor absorbed in the breadfruit chips agroindustry in one production process is 12 people with the absorption of labor by 0,55 percent.Keyword : Rentability, Employment, Agroindustry